Aligning content rendering resolution and feature size with display capability in near‐eye display systems. Issue 4 (28th March 2019) - Hoffman, David M.; McKenzie, Chris; Koprowski, Brion; Iqbal, Asif; Balram, Nikhil
Abstract: In order to create a satisfying experience with near‐eye displays, the content must be adapted to be legible on the display used. New displays are using subpixel arrangements that can limit the minimum resolvable feature size to something greater than with the conventional RGB stripe arrangement. We conducted an experiment to measure the minimum and preferred size of text in two virtual reality (VR) displays systems and find that the text size is display limited. We then measure several displays with different pixel arrangements to determine whether the subpixel arrangement could impact legibility. We propose several Fourier metrics that can be computed from the measured data to categorize the capability of the display and describe a framework for selecting the appropriate content from a set of discrete tiers. Abstract : For AR/VR systems, new subpixel arrangements can limit detail visibility compared with a display with RGB stripe arrangement. This paper describes work assessing the resolution for displays with nonconventional pixel arrangements and the associated artifacts. The work also proposes a framework for dividing AR/VR devices into tiers and setting an appropriate text size for good legibility.